Induksi Ginogenesis melalui Kultur Multi Ovule Slice dan Kultur Ovary Slice Dianthus chinensis - Kartikaningrum, Suskandari; Purwito, Agus; Wattimena, Gustaaf Adolf; Marwoto, Budi; Sukma, Dewi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2013)
Callus induction was studied in five genotypes of Dianthus chinensis using 2.4 D and NAA. Calluses can be obtainedfrom unfertilized ovule culture and ovary culture. The aim of the research was to study gynogenic potential and responseof Dianthus chinensis through ovule slice and ovary slice culture for obtaining haploid plants. Five genotypes of Dianthuschinensis and five media were used in ovule slice culture and two genotypes and three medium were used in ovary culture.Flower buds in the 7th stage were incubated for the purpose of dark pre-treatment at 4 oC for one day. Ovules and ovaries wereisolated and cultured in induction medium. Cultures were incubated for the purpose of dark pre-treatment at 4 oC for seven days, followed by 25 oC light incubation. The result showed that 2.4D was better than NAA in inducing callus. Percentage of regenerated calluses were produced in V11, V13 and V15 genotypes in M7 medium (MS + 2 mg L-1 2.4D + 1 mg L-1 BAP + 30 g L-1 sucrose and M10 medium (MS + 1 mg L-1 2.4D + 1 mg L-1 BAP + 20 g L-1 sucrose). All calluses originated from ovule and ovary cultures flowered prematurely. Double haploid (V11-34) were obtained from ovule slice culture based on PER (peroksidase) and EST (esterase) isoenzym marker.Keywords: ovule slice culture, ovary slice culture, callus, Dianthus sp., haploid